2016
DOI: 10.5194/angeo-34-1011-2016
|View full text |Cite
|
Sign up to set email alerts
|

Plasma fluctuations at the flanks of the Earth's magnetosheath at ion kinetic scales

Abstract: Abstract. We present a statistical study of the magnetosheath plasma fluctuation spectra at a high-frequency range (with frequencies from 0.01 to 10 Hz). Variations of ion flux value and its direction are considered. The direction of ion flux is characterized by a polar angle -the deviation of the ion flux vector from the Sun-Earth line. We consider 290 Fourier's spectra that can be described by two power laws with a break, i.e., a change of slope. The ion flux fluctuation spectra are shown to have breaks at h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 33 publications
(42 reference statements)
5
14
0
1
Order By: Relevance
“…Rakhmanova et al. (2016) showed that the polar angle fluctuation spectra are typically steeper than the spectra of the ion flux value fluctuations. This is also the case in the present study.…”
Section: Magnetosheath Crossingmentioning
confidence: 99%
See 2 more Smart Citations
“…Rakhmanova et al. (2016) showed that the polar angle fluctuation spectra are typically steeper than the spectra of the ion flux value fluctuations. This is also the case in the present study.…”
Section: Magnetosheath Crossingmentioning
confidence: 99%
“…Alexandrova et al. 2013; Bruno & Carbone 2013) and at the flank MSH (Alexandrova 2008; Rakhmanova, Riazantseva & Zastenker 2016; Riazantseva et al. 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kinetic‐scale plasma fluctuations have been explored systematically since 2011 with the help of the BMSW (Fast Solar Wind Monitor, Šafránková, Němeček, Přech, Zastenker, Cěrmák, et al, ; Zastenker et al, ) instrument on board Spektr‐R spacecraft. Parameters of plasma turbulence based on BMSW measurements were considered in the SW (Chen et al, ; Riazantseva et al, , , ; Šafránková, Němeček, Přech, & Zastenker, ; Šafránková et al, , ) as well as in the flank MSH (Rakhmanova et al, ; Rakhmanova, Riazantseva, Zastenker & Yermolaev, ; Riazantseva et al, , ). The BMSW data set covers 6 years of continuous plasma measurements in the SW and MSH that allow for statistical study of plasma fluctuations for various ambient conditions and upstream SW parameters.…”
Section: Introductionmentioning
confidence: 99%
“…2013 b , 2015, 2016; Riazantseva et al. 2015, 2016; Rakhmanova, Riazantseva & Zastenker 2016; Rakhmanova et al. 2017) allows us to expand our knowledge on processes in the dissipation range and in the transition region.…”
Section: Introductionmentioning
confidence: 99%